Flavonoid Naringenin: A Potential Immunomodulator for Chlamydia trachomatis Inflammation - Abebayehu N. Yilma; Shree R. Singh; Lisa Morici; Vida A. Dennis (Mediators of Inflammation)
Chlamydia trachomatis, the agent of bacterial sexually transmitted infections, can manifest itself as either acute cervicitis, pelvic inflammatory disease, or a chronic asymptomatic infection. Inflammation induced by C. trachomatis contributes greatly to the pathogenesis of disease. Here we evaluated the anti-inflammatory capacity of naringenin, a polyphenolic compound, to modulate inflammatory mediators produced by mouse J774 macrophages infected with live C. trachomatis. Infected macrophages produced a broad spectrum of inflammatory cytokines (GM-CSF, TNF, IL-1β, IL-1α, IL-6, IL-12p70, and IL-10) and chemokines (CCL4, CCL5, CXCL1, CXCL5, and CXCL10) which were downregulated by naringenin in a dose-dependent manner. Enhanced protein and mRNA gene transcript expressions of TLR2 and TLR4 in addition to the CD86 costimulatory molecule on infected macrophages were modulated by naringenin. Pathway-specific inhibition studies disclosed that p38 mitogen-activated-protein kinase (MAPK) is involved in the production of inflammatory mediators by infected macrophages. Notably, naringenin inhibited the ability of C. trachomatis to phosphorylate p38 in macrophages, suggesting a potential mechanism of its attenuation of concomitantly produced inflammatory mediators. Our data demonstrates that naringenin is an immunomodulator of inflammation triggered by C. trachomatis, which possibly may be mediated upstream by modulation of TLR2, TLR4, and CD86 receptors on infected macrophages and downstream via the p38 MAPK pathway.